The role of rivalry: Public goods versus common-pool resources - Frank P. Maier-Rigaud; Jose Apesteguia (Max Planck Institute for Research on Collective Goods, 2004)
Despite a large theoretical and empirical literature on public goods and common-pool resources, a systematic comparison of these two types of social dilemmas is lacking. In fact, there is considerable confusion about these two types of dilemma situations. As a result, they are often treated alike. In this paper we argue that the degree of rivalry is the fundamental difference between the two games. We show that rivalry implies that both games cannot be represented by the same game theoretic structure. Fur-thermore, we experimentally study behavior in a quadratic public good and a quadratic common-pool resource game with identical Pareto opti-mum but divergent interior Nash equilibria. The results show that partici-pants clearly perceive the differences in rivalry. Aggregate behavior in both games starts relatively close to Pareto efficiency and converges to the respective Nash equilibrium.
Keywords: 330; Öffentliche Güter; Gemeingüter; Gefangenendilemma; Test; Spieltheorie